Analysis of Working Decision of Elderly in Yogyakarta Province - Yozi Aulia Rahman, Yozi Aulia Rahman; Nindya Haryo Permadi, Nindya Haryo Permadi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This research aimed to analyse the the social-economis factors influencing the working decisions of elderly in Yogyakarta Province. The sample used was the elderly population of Special Region of Yogjakarta province aged 60 years amounted to 1.906 people following the number of respondents of Susenas in 2016. The analytical tool used is Binary Logit Regression using SPSS 21.The results show that the number of productive elderly people was 57,50% from the whole number of elderly people. The elderly workers dominantly work in the agriculture sector. Their profession is as an entrepreneur and mostly helped by their workers and others are as full time force workers. Binary regression test showed that duration of illness, hospitalization, dependent burden, living location, and pension guarantee significantly negative influence to their decision to go working. Meanwhile, level of primary education, marital status, and their status in the household positively significant influence to work. In addition, gender, level of secondary and higher education, and their household expenses do not significantly influence to their decision to work in the Special Region of Yogjakarta province in 2016.